PEMBELAJARAN BERBASIS PENDIDIKAN KARAKTER BERBAHAN AJAR PUISI DENGAN TEKNIK PEMBACAAN HEURISTIK-HERMENEUTIK - Suyitno Suyitno; Andayani Andayani; Nugraheni Eko (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis study aims to describe teachers’ understanding of: (a) a model of charactereducation-based learning using poems as learning materials, (b) the heuristic-hermeneuticreading technique in poetry learning, and (c) problems of character education usingpoems as learning materials supported by teachers’ critical attitudes and autonomousparticipation through the application of the heuristic-hermeneutic reading technique.The study employed the qualitative descriptive technique and was a preliminary studyas the first step of model development. The data sources were documents and eventsinvolving teachers and students at junior high schools in Karanganyar Regency. Theresults of the study are as follows. First, there is a gap between the phenomena expectedby the poetry learning using the heuristic-hermeunetic reading technique and the actualheuristic-hermeunetic reading technique in the field. Second, the gap is attributable toseveral factors, namely: (a) the initial competence in poetry learning, (b) poetry learningobjective setting, (c) poetry learning implementation, (d) poetry learning methods andstrategies, (e) poetry learning media, and (f) poetry learning evaluation.